PRAGMATIC STUDY: MAXIM VIOLATIONS IN THE CHRONICLES OF NARNIA: THE LION, THE WITCH AND THE WARDROBE MOVIE DIALOGUES - Luh Putu Angelina Septiani; Ni Nyoman Padmadewi (Undiksha Press, 2026)
This study investigates the violation of Grice’s conversational maxims in the movie “The Chronicles of Narnia: The Lion, the Witch, and the Wardrobe”. Grounded in Grice’s Cooperative Principle, this research focuses on identifying the types of maxim violations and explaining the communicative purposes behind their use in movie dialogues. A descriptive qualitative research design was employed, with data collected from selected utterances spoken by the main characters in the movie. The data were analyzed by classifying the violations into four types of maxims: quality, quantity, relation, and manner. These violations are used by the characters to convey implicit meanings, express emotions, and develop the storyline. The results of the study indicate that three types of maxim violations were identified: violations of the maxim of quality, the maxim of quantity, and the maxim of manner. Violations of the maxim of manner were the most prevalent. These violations serve to depict emotional conflict, conceal information, manipulate other characters, and advance the plot. These findings suggest that maxim violations in film dialogue are not merely a form of communication failure, but rather a communicative strategy that serves a specific pragmatic function.